“The Darkness”: Deprivation of sunlight as a form of torture - Jane Kilpatrick; Sondra Crosby; Brock Chisholm (Torture)
Introduction. Deprivation of sunlight (DoS) should be considered independently as a method of torture. We review the definition and the spectrum of DoS, and the harms it causes that may rise to the level of torture. Method. We review relevant international case law, and highlight how the harms of DoS have historically not been fully considered in torture cases, possibly legitimizing its use. Conclusion. A standardized definition of deprivation of sunlight be developed and included in the Torturing Environment Scale, we call for an explicit international prohibition of DoS. Keywords: Sunlight deprivation, torture, no-touch torture